A novelty in the genus Hechtia (Hechtioideae, Bromeliaceae) from Jalisco, Mexico - Flores-Argüelles, Alejandra; López-Ferrari, Ana Rosa; Espejo-Serna, Adolfo; Romero-Guzmán, Ariosto Rafael (Phytotaxa, 2019)
Hechtia ibugana a new species from the municipality of Puerto Vallarta, Jalisco, is described and illustrated. The new taxon is compared with H. pretiosa and H. rosea, species that also present sepals and petals rose to reddish, as well as with H. iltisii and H. santanae, endemic species of the state of Jalisco, Mexico.